Annatto seed by-product in diets containing sorghum for commercial laying hens - de Melo, Marcelle; Freitas, Ednardo; Dantas, Francisco Diego; Fernandes, Danilo; Watanabe, Pedro (Revista Ciência Agronômica, 2021)
This study aimed to evaluate the effect of including annatto seed by-product (ASB) in diets containing sorghum on nutrient utilization, performance and characteristics of the eggs of laying hens. A total of 288 Lohman Brown laying hens, 34 weeks of age, were distributed in completely randomized design with six treatments and six replications of the eight birds each other. The treatments consisted of a diet with corn as an energy source and other with sorghum and inclusion of 0, 25, 45, 65 and 85 g/kg of ASB. Comparing the results, increasing levels of RSU did not affect the metabolizability of nutrients, and utilization the energy of the feed. It was also observed there was no effect on the performance and parameters egg quality, except for yolk color. There was a significant linear increase in yolk colour with inclusion of ASB. We concluded that the annatto seed by-product can be used at levels up to 85 g/kg in laying hen diets containing sorghum as the main source of energy, with the possibility of reducing yolk pigmentation problems, caused by the total substitution of corn by sorghum, with the inclusion of ASB from 25 g/kg.